Thermal characteristics in turbulent channel flows with V-baffle vortex generators - Kaewkohkiat, Y.; Jedsadaratanachai, W.; Eiamsa-Ard, P.; Promvonge, P.; Eiamsa-Ard, S. (My University, 2014)
Experimental work has been performed to examine the effects of V-baffle vortex generators on the heat transfer and friction characteristics in a channel under a constant heat flux boundary condition. In the experiments, V-baffles at different pitch ratios (PR=P/e = 4.0, 6.0 and 8.0) were carried out. Measurements were carried out for a channel of one aspect ratio, AR = W/H = 4.0 and duct height, H= 40 mm with baffle height, e = 8 mm. Experiments were conducted for the Reynolds number range of 6000 to 22,000. The distributions of temperature and local Nusselt number on bottom channel wall were observed with thermochromic liquid crystal (TLC) sheet. Isothermal friction factors were also taken and presented. The obtained results demonstrate that heat transfer increases with the increase of Reynolds number, whereas friction factor (f) shows the opposite trend. Experimental results also show that the channels with V-baffle at the highest pitch ratio (PR = 8.0) provide highest heat transfer than others. © 2014 Asian Institute of Technology.
Keywords: Baffle; Channel; Heat transfer; Thermochromic liquid crystal